Community - Delanty, Gerard (Key ideas., 2003)
The increasing individualism of modern Western society has been accompanied by an enduring nostalgia for the idea of community as a source of security and belonging and, in recent years, as an alternative to the state as a basis for politics. Gerard Delanty begins this stimulating introduction to the concept with an analysis of the origins of the idea of community in Western Utopian thought, and as an imagined primitive state equated with traditional societies in classical sociology and anthropology. He goes on to chart the resurgence of the idea within communitarian thought, the compli.